Comparative Analysis of Income of Trolling Line and Set Longline Fishing Fishermen in Mallusetasi District, Barru Regency - Mas’ud, Rizka Maulidiyah; Baso, Aris; Adhawati, Sri Suro (Hasanuddin University, 2018)
Capture fisheries business is one of the coastal community business activities in Mallusetasi District which focuses on fish production by carrying out fishing activities in the sea using trolling line and set longline fishing gear. This study aims to comparative analysis of income of trolling line and set longline fishing rods so it can be used as a reference in the selection of effective and efficient fishing gear at Mallusetasi District, Barru Regency. This study was conducted in November 2017-January 2019 at Mallusetasi District. The data were analyzed using income analysis. This research is quantitative by using a survey method through interviews with a sample of 39 respondents and a set longline fishing rod fisherman totaled 19 respondents, so that the total sample is 50 respondents and observations using purposive sampling technique.. The results showed that the trolling line income was Rp 5.825.923 per month, while the total longline fishing line income was Rp 4.738.040 per month. This shows that the income of troll line fishermen is higher than long line fishing fishermen.